2014
DOI: 10.1002/dev.21206
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term influences of a preterm birth on movement organization and side specialization in children at 4–8 years of age

Abstract: This study explored upper-limb and head kinematics during unimanual goal-directed movements in children born preterm (PT) and full-term (FT) aged 4-8 years. Further, functional lateralization was investigated through side-specific kinematics and hand preference observations. Altogether, 141 children were included, divided into three sub-groups based on gestation week at birth (GW). Children born FT (38-41 GW) and moderately PT (33-35 GW) showed faster, smoother, and shorter movement trajectories than children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…with stroke demonstrate laterality of ULs in reaching to contact toys and less frequent manipulation of toys in the midline compared to healthy, term-born infants 177,178 ; and (ii) children aged four to eight years who were born preterm (<33 weeks GA) demonstrate laterality of ULs during reaching compared to healthy children born at term. 195 Findings of this study lend support to and extend on this earlier work by identifying asymmetries between ULs in unimanual contacts as early as 14 weeks C.A. and unimanual grasps at 18 weeks C.A.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…with stroke demonstrate laterality of ULs in reaching to contact toys and less frequent manipulation of toys in the midline compared to healthy, term-born infants 177,178 ; and (ii) children aged four to eight years who were born preterm (<33 weeks GA) demonstrate laterality of ULs during reaching compared to healthy children born at term. 195 Findings of this study lend support to and extend on this earlier work by identifying asymmetries between ULs in unimanual contacts as early as 14 weeks C.A. and unimanual grasps at 18 weeks C.A.…”
Section: Discussionsupporting
confidence: 83%
“…Findings indicate that preterm infants have: (i) less organised UL movements and laterality of ULs in reaching 195 ; (ii) less effective reaching strategies 181,196 ; (iii) slower UL movements and increased adjustments during reaching 197 ; (iv) impaired motor planning 198 ; (v) impaired motor control 199 ; and (vi) increased risk of motor coordination delays and impaired manual dexterity. 200 There remains, however, a paucity of literature examining the early development of reaching in infants with early brain injury.…”
Section: Early Longitudinal Upper Limb Development and Detection Of Dmentioning
confidence: 99%
“…Preterm babies are often delivered prematurely by their care-providers when there are signs of threat to life due to worsening hypoxia in utero. The hypoxia in these babies may similarly explain the phenomenon of up to twice the incidence of non-right handedness preterm babies compared to normal term babies 21,22 .…”
Section: The Hypothesismentioning
confidence: 98%
“…Motion analyses of reaching movements and visuo-manual aiming have shown promising results in characterizing the influence of premature birth on movement control, distinguishing between minor movement coordination problems and in identifying subtle sensorimotor impairments [Fallang et al, 2003;Johansson et al, 2014;Sagnol et al, 2007;Toledo and Tudella, 2008;Van Braeckel et al, 2008]. At preschool-and early school age, significant differences between children born very PT and those born at term regarding movement smoothness and segmentation have been demonstrated [Johansson et al, 2014]. Studies using 3D motion analysis involving children born PT have also reported less evident functional lateralization in terms of less apparent side differences during upper-limb performance compared with term born controls [Johansson et al, 2014;R€ onnqvist and Domell€ of, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…At preschool-and early school age, significant differences between children born very PT and those born at term regarding movement smoothness and segmentation have been demonstrated [Johansson et al, 2014]. Studies using 3D motion analysis involving children born PT have also reported less evident functional lateralization in terms of less apparent side differences during upper-limb performance compared with term born controls [Johansson et al, 2014;R€ onnqvist and Domell€ of, 2006]. Indeed, whilst approximately 90% of typically developing school children manifest a right hand preference [Szaflarski et al, 2012], a recent meta-analysis suggests that the rate of right-hand r Lenfeldt et al r r 5052 r preference is lower among children born PT (63%-92%), even in cases where no developmental deviation is present [Domell€ of et al, 2011].…”
Section: Introductionmentioning
confidence: 99%